A fresh start in Egypt? Actors, interests, scenarios - Muriel Asseburg; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2011)
President Hosni Mubarak's ouster is a historical turning point for Egypt. The assumption of power by the Supreme Council of the Armed Forces could bring about a political opening of the country, but this is by no means assured. Egypt's future is not, however, solely dependent on whether the military delivers on its promises in regard to constitutional amendments, free elections, and the transfer of power to a civilian government. The opposition forces must also come forward with concrete visions of what the country's future political system should look like. They must also organise themselves so as to be able to feed their demands into the process. But which interests are the various actors pursuing? How are they organised and how are power relations shaped among them? And what potential scenarios for Egypt's future can be derived from this? One thing is already clear: without broad international support, it will be impossible to manage the transition process. This presents German and European policymakers with the opportunity to support genuine democratisation
Keywords: 320